Pendampingan Pembelajaran Al-Qur’an Di Masjid Al-Iqra Desa Meok Kec. Enggano Kab. Bengkulu Utara - Witama, Muhammad Faizal; Melyasari, Eliza; Sari, Dewa Ayu Purnama; Sari, Prima Dwi Putri; Yati, Harlinda; Khoirun, Alfa Ridzi Misbaqul; Setiawan, Dimas; Kurniawan, Ego; Rahmadaniati, Rossa; Erliyanti, Junita; Wati, Devi Setia (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2024)
This study examines the community service activities conducted by the State Islamic University (UIN) Fatmawati Sukarno Bengkulu in Desa Meok, Enggano District, North Bengkulu Regency, from July 3 to August 22, 2024. The program aims to enhance the Quran reading skills of children in the minority Muslim community by applying the iqra' method. Developed by KH. As’ad Humam, the iqra' method emphasizes direct practice of reading hijaiyyah letters without spelling, facilitating learning for students at various levels of understanding. Assistance was provided from Monday to Thursday, beginning with the recitation of Surah Al-Fatihah and a prayer before learning, and concluding with a Quran completion prayer. Observations revealed significant challenges, including a limited number of teachers, frequent changes in instructors, and constraints in the teachers' ability to teach the Quran. Out of 17 students, 14 were at the iqra' stage while 3 had begun reading the Quran. The Participatory Action Research (PAR) method was employed to enable continuous evaluation and improvement in the learning process, involving all stakeholders to understand and address existing issues. This program is expected to enhance teaching effectiveness, help the children in Desa Meok develop a love for and understanding of the Quran, and motivate them to continue learning and deepening their religious knowledge. In addition to Quranic education, the initiative also aims to strengthen spiritual connections and worship habits among the children, which is crucial for their character and faith development